Childhood adversity among institutionalized male juvenile offenders and other high-risk groups without offense records in Portugal - Pinto, Ricardo José (2015)
The literature has shown that delinquent adolescents report high rates of childhood adversity and family dysfunction. However, it is important to know both the degree of adversity among delinquent adolescents in comparison with other high-risk samples and the contribution of each single form of adversity to this comparison. The purpose of this study was to evaluate childhood adversity, psychopathology, and risk behaviors among 4 high-risk groups, including incarcerated delinquent youths. The participants were 120 male youths between 13 and 19 years old (M = 16.18, SD = 1.26), including 30 youths who were arrested and held in detention centers as a consequence of violent crimes; 30 youths who were identified by Child Protective Services (CPS) and remained with their families; 30 youths who were identified by CPS, removed from their homes, and placed in child and youth residential care; and 30 youths who were randomly selected from schools. The incarcerated youths reported significantly more adversity, global psychopathology, and global index of risk behaviors. When considering each risk behavior, the incarcerated youths reported higher percentages of alcohol abuse, drug use, early smoking initiation, physical assault, carrying weapons, early initiation of sexual intercourse, sexual intercourse under the influence of drugs, and sexual intercourse without condom use. The logistic regression analyses showed that only emotional neglect was significantly associated with delinquency. This study suggests that delinquent youths are exposed to a great magnitude of adversities in childhood, with emotional neglect as an independent risk factor for delinquency. In addition, these youths have higher rates of psychopathology and risk behaviors compared to other high-risk samples.